IMAGINING HELL: A BURKEIAN ANALYSIS OF INDONESIAN RELIGIOUS AFTERLIFE IMAGES - Peter Suwarno (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2012)
This paper is not only dealing with depiction of hell (divine punishment) which is very popular depicted by the speech and media news in Indonesia, but also description on meaning, and the possibility on motive behind that description. Applying Burke theory on logology, this paper revealed that the depiction of hell punishment constituted the ritual of purity. Based on the cycle of order, feeling of guilty, redemption through sacrifice to achieve the purity, general depiction on hell are a reflection of the challenges and complexity of legal rules and regulation that exactly will be broken off. This violation of the rule creates a sense of guilty and sin which come out as all the problems and difficulties that the majority of Indonesian must hold – the situation that generates scapegoat. The victims of the scapegoat became the apparent sinners, and the punishment is the sacrifaction which create satisfaction and a sense of clean up.***Tulisan ini tidak hanya untuk membahas penggambaran neraka (hukuman akhirat) yang sangat populer sebagaimana digambarkan dalam pidato dan media di Indonesia, tetapi juga untuk mengungkapkan makna dan kemungkinan motif di balik gambaran tersebut. Dengan teori logologi Burke, tulisan ini mengungkapkan bahwa penggambaran siksaan neraka merupakan ritual pemurnian. Berdasarkan siklus ketertiban, rasa bersalah, penebusan melalui pengorbanan untuk mencapai kemurnian, gambaran hukuman di neraka adalah cerminan dari tantangan dan kompleksitas aturan dan hukum yang pasti akan dilanggar. Pelanggaran ini menciptakan rasa bersalah dan dosa yang diwujudkan dalam bentuk semua masalah dan kesulitan bahwa mayoritas penduduk Indonesia harus tahan-situasi yang menimbulkan kambing hitam. Para korban yang merupakan kambing hitam menjadi orang berdosa terkutuk, yang hukumannya merupakan sebuah pengorbanan, menciptakan kepuasan dan rasa dibersihkan.